A Study of Platelet Activation during Human Cardiopulmonary Bypass and the Effect of S-Nitrosoglutathione - Langford, Edward J; Parfitt, Andrew; de Beider, Adam J; Marrinan, Michael T; Martin, John F (Thrombosis and Haemostasis, 1997)
Cardiac surgery is complicated by the occurrence of post-operative bleeding due to platelet dysfunction. This is largely caused by platelet activation and consumption during cardiopulmonary bypass. Patients undergoing cardiac surgery requiring cardiopulmonary bypass were studied to determine whether early platelet changes due to bypass could be inhibited using the platelet-selective nitric oxide donor S-nitroso-glutathione (GSNO). Flow cytometry was used to measure platelet surface expression of P-selectin (an α-granule protein) and glycoproteins (GP) IIb/IIIa and Ib (mediators of aggregation and adhesion) before and 5 and 10 min after commencing cardiopulmonary bypass, in 6 controls and 6 patients receiving GSNO 50 μg/min. Platelet P-selectin expression increased during bypass both in controls and patients receiving GSNO. Glycoproteins IIb/IIIa and Ib fell during bypass in control and GSNO-treated patients. There was no difference between control and GSNO-treated groups. Thus no significant platelet inhibition by S-nitrosoglutathione was demonstrated under these conditions.